FSKKP tracer study management system - Nur Syuhada, Anuar (2019)
This is a review for Graduate Verification (KPG) which is a manual system that has been set up to track the prospects of local IPT graduates before attending their respective convocation ceremonies. Therefore, the Graduate Certification Study in a more effective system by using the computer to find out the relevant statistics of the graduates. Previous surveys were conducted online via the official website as a step for graduates to fill out survey questions. After completing the survey, graduates are required to print an attachment or boring that should be submitted on graduation day, where it is inconvenient for the student to bring the print to the day of the incident. Through this system, it is used by lecturers to make it easier for them to review the student's information. It is also used by the Ministry of Higher Education (KPT) to identify the first destination of graduates at the Certificate and above. Through this system, the Ministry of Higher Education can find out basic things related to the new graduates' nature of employment. Rapid Application Development (RAD) is a methodology used to develop this application. The RAD methodology consists of four main stages, the first is the level of planning requirements, the user design stage, the stage of construction, and the final cutting stage. After application has been developed, customers will be given a user acceptance test (UAT) to ensure that all functionalities function as needed without any mistake. The UAT test will ensure that the application meets all the objectives and can be used to solve current problems.